“You ought to stop trying because you had too many birthdays?” – Heroic Male Aging in the Rocky Films - Nina Schnieder (Current Objectives of Postgraduate American Studies)
This essay deals with one of Hollywood’s most popular action heroes, Rocky Balboa. It discusses the whole Rocky“ franchise as six age narratives in which the athletic protagonist faces the obstacles of age. By looking at male identity especially with regard to retirement and the aging male body, the depiction of male aging and what it signifies in these sport action films will be discussed.